2009
DOI: 10.1002/pen.21459
|View full text |Cite
|
Sign up to set email alerts
|

Experimental analysis for extrusion screw geometry to produce highly transparent polypropylene sheets

Abstract: The observation was experimentally conducted by using many screws with various geometries to obtain a highly transparent polypropylene melt resin sheet. The pressure distribution in the extruder, melt temperature profile across melt flow, the extruder throughput and the specific energy consumption were monitored. In a preliminary evaluation, transparent melt web was obtained in a simple straight channel depth screw and a straight channel depth screw with a torpedo type barrier section. The transparency of melt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The quality of rubber product has caused more and more attention, and so the research on thermal deformation of barrel has become a hot-point project. According to research indicated that the asymmetry of temperature contributes increasing in grid of temperature and thermal stress easily, that engender thermal deformation in barrel of big extruder [2][3][4]. In big extruder SJ150×25, this phenomenon not only increase error of coaxial degree between screw and barrels, but also aggravate the screw often rubs against barrel.…”
Section: Introductionmentioning
confidence: 99%
“…The quality of rubber product has caused more and more attention, and so the research on thermal deformation of barrel has become a hot-point project. According to research indicated that the asymmetry of temperature contributes increasing in grid of temperature and thermal stress easily, that engender thermal deformation in barrel of big extruder [2][3][4]. In big extruder SJ150×25, this phenomenon not only increase error of coaxial degree between screw and barrels, but also aggravate the screw often rubs against barrel.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous article, we experimentally conducted the extrusion tests by using many screws with various geometries to obtain a highly transparent PP melt resin sheet before its solidification [50]. The transparency of melted resin sheet was obtained by the screw geometry so that the specific energy consumption was small and the melted temperature was low.…”
Section: Introductionmentioning
confidence: 99%